Effect of construction technology on air-lifting pump mining - Zhao, Yan-Lin; Wang, Xia-Guang; Tang, Chuan-Lin; Hu, Dong; Lin, Peng; Xia, Mei-Li (Frontiers in Earth Science, 2023)
The air-lifting pump has the advantages of low cost, strong reliability, simple structure and convenient maintenance, especially in the fields of deep-sea mining, oilfield mining and mineral mining under complex geological conditions. The construction technology and air intake mode not only play a decisive role in the performance of the air-lifting pump, but also greatly hinder the engineering application of the air-lifting pump. Here, the air-lifting pump is taken as the research object, and the river sand is used as the experimental transport medium. The particle concentration-efficiency model is established based on the mechanical energy conservation theorem. The working performance characteristic parameters of the air-lifting pump under different construction technologies are obtained by a three-axis motion control system. On this basis, the working performance characteristic parameters of the air-lifting pump under different intake modes are obtained by changing the intake mode. The results show that the particle concentration-efficiency model can well describe the efficiency of lifting solid particles by the air-lifting pump. When the sand depth is less than 200 mm, the concentration and efficiency of solid particles transported by the air-lifting pump in the horizontal movement construction are significantly better than those in the fixed position construction. In the same construction technology, the solid particle concentration of the air-lifting pump in uniform intake mode is better than that in non-uniform intake mode, while the transportation efficiency of the air-lifting pump in non-uniform intake mode is better than that in uniform intake mode. The research results of this paper can provide an important theoretical reference value for the air-lifting pump in practical engineering applications.